Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

a) Let $L:V \to V$ be a linear map such that $L^2 + 2L + I = 0$, show that $L$ is invertible.
b) Let $L:V \to V$ be a linear map such that $L^3 = 0$, show that $I - L$ is invertible.

Here, $I$ is identity mapping.

For first part, I know that $L^2 + 2L + I = (L+I)^2 = 0$, if $v\in V$ then $(L+I)^2 v = (L+I)(L(v) + v)) = 0$ so $L(v) + v$ is in null space of $L+I$, from here how do I show that $0$ is only in null space of $L$.

I don't need exact solution. Hints would suffice.

share|improve this question

7 Answers 7

up vote 7 down vote accepted

a) Suppose that $Lv=0$ then $0 = L^2v +2Lv+v = L0 + 0 + v = v$ i.e. $v=0$.

b) Suppose $(I-L)v=0$ i.e $Lv = v$ hence $0 = L^3 v =v$ i.e. $v=0$

share|improve this answer

$L^2 + 2L + I = O$ then $-L^2-2l=I$ then $L(-L-2)=I$ therfore $$L^{-1} =-L-2$$

share|improve this answer

Hint: You can show that if $L$ is an endomorphism and $P$ is a polynomial such that $P(0) \neq 0$ and $P(L)=0$, then $L$ is invertible.

share|improve this answer
    
i guess this is little complicated, since I haven't gone far as to read endomorphism. Still thank you very much for your effort. –  hasExams Jan 29 '13 at 21:54
    
@testuser: In fact, it is quite simple. For your example $L^2+2L+I=0$, just notice that $-L(L+2I)=I$. –  Seirios Jan 29 '13 at 21:57
    
Yep, it is :) ... only I could have realized sooner!! –  hasExams Jan 29 '13 at 22:03

For the first one you have $$ L(L + 2I) = -I. $$ For the second one you have $$ (I-L)(I+L)(I+L^2) = \dots = I. $$

share|improve this answer

Yet another approach for a), although it might be overkill:

Let $p(X) := X^2 + 2X + 1$. As $p(L)=0$, the minimal polynomial of $L$ divides $p$. Conclude that $0$ is not an eigenvalue of $L$.

share|improve this answer
    
I very much like this approach, it is very natural. –  Ragib Zaman Jan 30 '13 at 1:48

For the second you should use the property: $(1-x)(1+x+x^2)=1-x^3$.

share|improve this answer

The same proposition deals with both parts:

If $L^n=0$ for some $n\in \mathbb{N}$ then $I-L$ is invertible. To prove this, check that $I+L+L^2 + \cdots + L^{n-1}$ is the inverse.

a) $(L+I)^2=0$ so $I-(L+I) = -L$ is invertible, and hence so is $L.$

b) is precisely the case $n=3.$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.